Mapping the evidence on post-intensive care syndrome in paediatric populations: A scoping review protocol - Shoheb Hassan; Ali Hassan (PLoS ONE, 2026)
Objective This scoping review aims to comprehensively map the primary literature on post-intensive care syndrome in paediatric populations (PICS-p), across all recognised PICS-p domains, with a focus on diagnostic methodologies, preventive and therapeutic interventions, and reported post-ICU outcomes among children aged 1 month–18 years. Introduction Post-intensive care syndrome (PICS) encompasses new or worsening physical, cognitive, psychological, or social impairments emerging after critical illness. While extensively studied in adults, its paediatric counterpart, PICS-p, remains under-recognised and inconsistently characterised. Children surviving paediatric intensive care may face long-term functional limitations, developmental challenges, and psychosocial difficulties, with substantial implications for families and caregivers. Existing evidence is fragmented across diverse clinical contexts, age groups, and outcome measures, and no comprehensive synthesis has mapped how PICS-p is assessed, managed, or monitored. A structured overview is needed to clarify current practice, highlight gaps, and inform future research and clinical pathways. Inclusion criteria We will include primary clinical studies involving paediatric patients aged 1 month–18 years who have survived admission to a paediatric or specialised intensive care unit. Eligible studies may evaluate diagnostic or screening tools, preventive or therapeutic interventions, or longitudinal outcomes related to PICS-p. Studies including mixed-age populations will be incorporated only when paediatric data are reported separately or can be disaggregated. Grey literature reporting primary clinical data will be included. Exclusions apply to neonatal-only cohorts, adult-only studies, abstract-only publications, non-clinical reports, and studies focusing solely on in-ICU outcomes without post-discharge assessment. Only English-language studies published from 1 January 2000 onward will be considered. Methods Following PRISMA-ScR and Joanna Briggs Institute guidance, this scoping review will conduct systematic searches across PubMed, Scopus, the Cochrane Library, ProQuest, CINAHL, medRxiv, and major clinical trial registries. Searches will be limited to English-language studies published from 1 January 2000 to the date of search. All records will be deduplicated in Zotero, and title/abstract and full-text screening will be performed independently by two reviewers using Rayyan, with discrepancies resolved by consensus or adjudication by a third independent reviewer. Data will be charted using a structured Microsoft Excel form and synthesised descriptively in tables and narrative summaries.